Artemis Fowl : The Arctic Incident - Colfer, Eoin (London Puffin Books, 2002)
Someone has been supplying Class A illegal human power sources to the goblins. Captain Holly Short of the LEPrecon Unit is sure that the person responsible is her arch-enemy, thirteen-year-old Artemis Fowl. But is he? Artemis has his own problems to deal with: his father is being held to ransom and only a miracle will save him. Maybe this time a brilliant plan just won't be enough.
Keywords: Magic -- Fairies -- Gifted Children -- Fiction